A molecular approach towards the taxonomy of fresh water prawns Macrobrachium striatum and M. equidens (decapoda, palaemonidae) using mitochondrial markers - Deepak Jose (2018)
© 2015 Informa UK Ltd. Genus Macrobrachium includes freshwater prawns which inhabit most diverse habitats ranging from low saline areas to inland hill streams and impounded water bodies. Being morphologically conserved, this genus has been exposed to severe disputes related to their taxonomy, systematics and phylogeny. Macrobrachium striatum and M. equidens represent two morphologically related congeneric species within this genus. Earlier, M. striatum was considered as a striped form of M. equidens. Though these species are now well-described morphologically and differentiated into two species, no molecular level investigation has been carried out in support of their speciation. We report a study on M. striatum and M. equidens with emphasis to their molecular data through mitochondrial markers (16S ribosomal RNA and cytochrome oxidase subunit I). Results obtained from developed molecular markers of the two species revealed considerable genetic differentiation between them. Phylogram generated using Minimum evolution and Neighbour joining analyses differentiated M. striatum and M. equidens as two independent species. Genetic distance data showed high interspecific divergence (ranging from 3.9% to 17.0% for 16S rRNA sequences and 13.8% to 21.0% for COI sequences) between M. striatum and M. equidens confirming the findings of phylogram. Hence, it could be delineated that M. striatum and M. equidens represent two distinct species within genus Macrobrachium with emphasis to their morphology and genetics.